2008
DOI: 10.1073/pnas.0806499105
|View full text |Cite
|
Sign up to set email alerts
|

Functional stoichiometry of the unitary calcium-release-activated calcium channel

Abstract: Two proteins, STIM1 in the endoplasmic reticulum and Orai1 in the plasma membrane, are required for the activation of Ca 2؉ releaseactivated Ca 2؉ (CRAC) channels at the cell surface. How these proteins interact to assemble functional CRAC channels has remained uncertain. Here, we determine how many Orai1 and STIM1 molecules are required to form a functional CRAC channel. We engineered several genetically expressed fluorescent Orai1 tandem multimers and a fluorescent, constitutively active STIM1 mutant. The ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
252
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 238 publications
(275 citation statements)
references
References 34 publications
17
252
3
Order By: Relevance
“…The CAD fragment forms a tetramer in solution ), whereas the longer STIM1 cytosolic fragments generally appear as dimers (Ji et al 2008;Penna et al 2008;Muik et al 2009;Yuan et al 2009;Zhou et al 2010a) that may need to unfold to expose the CAD and activate Orai1 (Korzeniowski et al 2010;Muik et al 2011). These findings raise the intriguing possibility that on store depletion, STIM1 undergoes a conformational change that results in formation of a tetramer through interactions among multiple CADs (Covington et al 2010), an idea that remains to be tested.…”
Section: Accumulation and Activation Of Crac Channels At Er-pm Junctionsmentioning
confidence: 91%
“…The CAD fragment forms a tetramer in solution ), whereas the longer STIM1 cytosolic fragments generally appear as dimers (Ji et al 2008;Penna et al 2008;Muik et al 2009;Yuan et al 2009;Zhou et al 2010a) that may need to unfold to expose the CAD and activate Orai1 (Korzeniowski et al 2010;Muik et al 2011). These findings raise the intriguing possibility that on store depletion, STIM1 undergoes a conformational change that results in formation of a tetramer through interactions among multiple CADs (Covington et al 2010), an idea that remains to be tested.…”
Section: Accumulation and Activation Of Crac Channels At Er-pm Junctionsmentioning
confidence: 91%
“…It has been demonstrated that the statistical analysis of bleaching steps of GFP-fused membrane proteins is a new way to determine the subunit stoichiometry of membranebound proteins [10,11]. From the distribution of the photobleaching steps of TβRI-GFP spots on HeLa cell membranes (from 13 cells), we found 82.1% (487 of 589 spots) bleached in one step, and 16.1% (92 of 589) bleached in two steps ( Figure 1B, 1C and Supplementary information, Figure S2).…”
Section: Monomeric Tβri In the Resting Cells At A Low Receptor Densitymentioning
confidence: 99%
“…Recent advances in single-molecule fluorescence imaging have offered a new way to analyze membrane proteins with ultrasensitivity and probe their stoichiometry in intact cells [10][11][12][13][14]. Using green fluorescent protein (GFP) to label the membrane proteins, stepwise photobleaching curves of individual proteins are counted, and a binomial distribution of photobleaching steps is obtained to investigate protein stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…The mEGFP tags were fused to the C-terminus of TASK3 channels and the N-terminus of the VSDs in KT channels, respectively ( Figure 2C and 2D). To maintain the density of channels low enough to minimize the chance of incidental overlap of two or more channels within a diffraction-limited area, the cells expressing TASK3 or KT channels were fixed only 3-5 h after transfection and examined by TIRF microcopy, as previously described [26,27]. In the quiescent cells, the exogenously expressed channels exhibited a punctate appearance of fluorescence on the membrane surface.…”
Section: One Kt Channel Consists Of Two Vsdsmentioning
confidence: 99%
“…For each identified trace, the bleaching steps were determined manually by one investigator and rescored blindly by another. Other criteria were as described in [26].…”
Section: Single-molecule Imagingmentioning
confidence: 99%